The role of autonomous energy production systems in urban energy networks. (19th September 2016) - Volpe, Rosaria; Frasca, Mattia; Fichera, Alberto; Fortuna, Luigi
Abstract : The technological and normative scenario of energy distribution systems is rapidly changing, evolving from a hierarchical rigid structure to a more flexible and rich topology including autonomous energy production systems. In this paper, with a mathematical model based on complex networks we study how user efficient systems, that is, systems with renewable energy resources directly exchanging the electrical energy with private connections among geographically neighbouring users, impact the electrical energy distribution in an urban territory. The mathematical model calculates the flow distribution in the network and, from this, a measure of the efficiency of local interconnections is derived. Several scenarios are considered, including the case where the nodes with renewable energy production systems are randomly placed in the territory and that where their positions are correlated as due to social effects or territory characteristics. The results reveal a non-trivial dependence of the model from its parameters and a decrease of the potential benefits of the introduction of user efficient systems when their sites have significant spatial correlations.